2019
DOI: 10.7717/peerj.8043
|View full text |Cite
|
Sign up to set email alerts
|

Improving the prediction accuracy of river inflow using two data pre-processing techniques coupled with data-driven model

Abstract: River inflow prediction plays an important role in water resources management and power-generating systems. But the noises and multi-scale nature of river inflow data adds an extra layer of complexity towards accurate predictive model. To overcome this issue, we proposed a hybrid model, Variational Mode Decomposition (VMD), based on a singular spectrum analysis (SSA) denoising technique. First, SSA his applied to denoise the river inflow data. Second, VMD, a signal processing technique, is employed to decompos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Nazir et al, in 2019, employed Variational Mode Decomposition (VMD) model that is based on a denoising technique called singular spectrum analysis (SSA), Empirical Bayes Threshold (EBT), and Support Vector Machine (SVM). 37 They applied these models to predict the daily river inflow of the Indus River Basin and compared the proposed model with others. Results showed that the suggested gave superior results and is validated for power-generating systems and water resources management.…”
Section: Introductionmentioning
confidence: 99%
“…Nazir et al, in 2019, employed Variational Mode Decomposition (VMD) model that is based on a denoising technique called singular spectrum analysis (SSA), Empirical Bayes Threshold (EBT), and Support Vector Machine (SVM). 37 They applied these models to predict the daily river inflow of the Indus River Basin and compared the proposed model with others. Results showed that the suggested gave superior results and is validated for power-generating systems and water resources management.…”
Section: Introductionmentioning
confidence: 99%
“…Adarsh et al [21] adopted the multivariate empirical mode decomposition (MEMD) to perform the multiscale characterization of hydroclimatic time series, where the forecasting accuracy is significantly improved. Nazir et al [22] compared the improvements achieved by the combined models adopting empirical mode decomposition (EMD), ensemble empirical mode decomposition (EEMD) and variational mode decomposition (VMD), where the evaluations for the results illustrate that the VMD-based model possesses higher prediction previous. For the well-investigated decomposition approaches including EMD, EEMD and VMD, the modalaliasing that is existed in EMD and is modified by EEMD to some extent may pose a challenge of accurate prediction for the decomposed components.…”
Section: Introductionmentioning
confidence: 99%